A STUDY ON THE EFFECT OF YOGIC INTERVENTION ON SELF CONFIDENCE AND EMOTIONAL INTELLIGENCE OF ADOLESCENTS - Mr. Kapil Dev (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2013)
The present study was undertaken to study the effectof yogic intervention on self-confidence and emotional intelligence of adolescents. The study was conducted on a sample of 200 adolescents in the age range of 13 to 18 years. The participants were divided into experimental and control groups. Experimental group received a yogic intervention. Agnihotri Self-confidence Inventory and Emotional Intelligence Scale by Dr. Sheetla Prasad were used to assess self-confidence and emotional intelligence of the sample.In this studyt-test was applied to compare the significance of difference between means of the experimental and control groups before and after yogic intervention.The results obtained shown that 90 days yogic intervention enhanced the self-confidence (t (200,198) = 11.823, p<.001), and emotional intelligence (t (200,198) = 9.262, p<.001) of the participants. Keywords: Adolescents, Yogic intervention, self-confidence, emotional intelligence.